Pengaruh Hubungan Interpersonal Guru-Siswa Dan Lingkungan Sekolah Terhadap Motivasi Belajar Siswa Di SMK Negeri 1 Banyudono - Rhosi Rahmawati; Anton Subarno; Subroto Rapih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine: 1) the effect of teacher-student interpersonal relationship on learning motivation, 2) the effect of school environment on learning motivation and 3) the effect of teacher-student interpersonal relationship and school environment on student learning motivation at SMK Negeri 1 Banyudono. This research is quantitative research with a correlational method. The subject of this research is students of SMK Negeri 1 Banyudono. The sampling technique used on this research is stratified random sampling. Data collection technique using a questionnaire. The instrument validation technique used on this research is validity test and reliability test. Data analysis includes classical assumption tests, such as normality tests, linearity tests and multicollinearity tests and there are hypothesis tests such as t-test, F-test, coefficient of determination, multiple regression analysis, effective contribution and relative contribution. The results of this research are: First, that there is a positive and significant influence of the teacher-student interpersonal relationship variable on student learning motivation at SMK Negeri 1 Banyudoni. This is evidenced by the value of Tvalue > Ttable 6.67 > 1.98 and a significance value of <0.05. So H0 is rejected and H1 is accepted. Second, it was found that there was no significant influence of school environmental variables on student learning motivation at SMK Negeri 1 Banyudono but the results still showed in a positive direction. This is proven by the significance value of the school environment of > 0.05 and the T value of 0.56 < T table of 1.98 so that H0 is accepted and H2 is rejected. Third, there is a positive and significant influence of teacher-student interpersonal relationship variables and the school environment together on student learning motivation at SMK Negeri 1 Banyudono. This is evidenced by the results of the F test with a F value of 34.75 > 3.09 F table with a significance level <0.05. So H0 is rejected and H3 is accepted. The results of multiple linear regression analysis show a coefficient of determination value of 0.438, where teacher-student interpersonal relationships and the school environment together influence student learning motivation by 43.8%. While the remaining 56.2% is influenced by other factors. Teachers should be active in participating in communication competency training in order to improve teacher-student interpersonal relationships and teachers pay more attention to all students.